2008
DOI: 10.1039/b709810c
|View full text |Cite
|
Sign up to set email alerts
|

An eight-connected 3D lead(ii) metal–organic framework with octanuclear lead(ii) as a secondary building unit: synthesis, characterization and luminescent property

Abstract: A novel 3D lead(II) metal-organic framework {Pb 4 (Bdc) 3 -(m 4 -O)(H 2 O)} n (1) (H 2 Bdc = isophthalic acid) with octanuclear [Pb 8 (Bdc) 6 (m 4 -O) 2 (H 2 O) 2 ] as secondary building units (SBUs) has been obtained and fully characterized by single crystal X-ray diffraction, IR, elemental analysis, TG-DTA and fluorescent spectra. XRD results indicate octanuclear lead(II) SBU contains two inversely related [Pb 4 (m 4 -O)] cores and is extended topologically into an infinite eight-connected bcu-type network v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(46 citation statements)
references
References 32 publications
(14 reference statements)
4
41
0
1
Order By: Relevance
“…To understand the nature of the two emission bands, we analyzed the photoluminescence properties of the L ligand and found that the strongest emission peak for L is at about 404 nm (l ex = 344 nm). Moreover, solid-state aromatic carboxylate ligands can also exhibit fluorescent properties at room temperature reported by the literature, the main emission peak for 1,3-H 2 BDC is located at 370 nm (l ex = 327 nm) [50], 1,4-H 2 BDC is located at 380 nm (l ex = 350 nm) [51], H 3 BTC is located at 380 nm (l ex = 334 nm) [52], H 4 BTEC is located at 370 nm Fig. 6.…”
Section: Solid-state Fluorescence Spectroscopymentioning
confidence: 97%
“…To understand the nature of the two emission bands, we analyzed the photoluminescence properties of the L ligand and found that the strongest emission peak for L is at about 404 nm (l ex = 344 nm). Moreover, solid-state aromatic carboxylate ligands can also exhibit fluorescent properties at room temperature reported by the literature, the main emission peak for 1,3-H 2 BDC is located at 370 nm (l ex = 327 nm) [50], 1,4-H 2 BDC is located at 380 nm (l ex = 350 nm) [51], H 3 BTC is located at 380 nm (l ex = 334 nm) [52], H 4 BTEC is located at 370 nm Fig. 6.…”
Section: Solid-state Fluorescence Spectroscopymentioning
confidence: 97%
“…Thus, a Pb 2 + -MOF based on benzenetricarboxylate shows emission attributed to a charge transfer from the ligand to the metal. [ 65 ] …”
Section: Luminescencementioning
confidence: 97%
“…Compared with that of transition metal complexes of dicarboxylates, the chemistry of the main group metal dicarboxylates is less explored [5]. On the other hand, some Pb(II) carboxylate compounds have exhibited various luminescent properties [14][15][16]. Although there are also some examples related to Pb(II) complexes of dicarboxylates with common spacers such as 1,4-BDC [3,17,18], À O 2 C-ðCH 2 Þ n -CO À 2 (n = 2-4) [18], 1,2-cyclohexanedicarboxylate (1,2-CHDC) and 1,3-CHDC [19], 1,4-naphthalenedicarboxylate (NDC) [14], the Pb(II) complexes of dicarboxylates with other spacers are still limited in number.…”
Section: -Carboxycinnamic Acid Lead(ii)mentioning
confidence: 99%
“…The assembly of metal-organic frameworks (MOFs) from dicarboxylate ligands has been of interest in recent years due to their structural chemistry [1][2][3][4][5][6][7][8][9][10][11] and their physical and chemical properties [1,3,[12][13][14][15][16]. Among these complexes, factors related to the spacer between the two carboxylate ends of the dicarboxylate ligand, e.g.…”
Section: -Carboxycinnamic Acid Lead(ii)mentioning
confidence: 99%